Growth Mechanism of Single-Walled Carbon Nanotubes from Pt Catalysts by Alcohol Catalytic CVD. Issue 1752 (6th February 2015) - Araujo, P.T.; Franklin, A.D.; Kim, Y.A.; Krueger, M.; Maruyama, Takahiro; Kondo, Hiroki; Kozawa, Akinari; Saida, Takahiro; Naritsuka, Shigeya; Iijima, Sumio
ABSTRACT Single-walled carbon nanotube (SWCNT) growth from Pt catalysts by an alcohol gas source method, a type of cold-wall chemical vapor deposition (CVD), was investigated. Raman results showed that the diameters of SWCNTs grown from Pt were below 1.2 nm, while transmission electron microscopy (TEM) showed that the diameters of most Pt catalyst particles were above 1.2 nm. This suggests that SWCNT diameters were smaller than Pt catalysts particles. X-ray photoelectron spectroscopy measurements showed that reduction of Pt particles occurred during the SWCNT growth. Based on these experimental data, growth mechanism of SWCNTs was discussed.